Thermal Treatment of Cerium Oxide and Its Properties: Adsorption Ability versus Degradation Efficiency - Pavel Janoš; Tomáš Hladík; Martin Kormunda; Jakub Ederer; Martin Šťastný (Advances in Materials Science and Engineering)
Cerium oxide belongs to the most important heterogeneous catalysts, but its applicability as so-called reactive sorbent for the degradation of toxic chemicals was only recently discovered. For these purposes, cerium oxide is prepared by precipitation of insoluble cerium salts (carbonates) with a subsequent thermal decomposition. Properties of cerium oxide prepared from the carbonate precursor are strongly affected by the temperature during the calcination. Main physicochemical properties of cerium oxide (specific surface area, crystallinity, and surface chemistry) were examined in dependence on the calcination temperature. As the adsorptive properties of CeO2 are undoubtedly of great importance in the abovementioned applications, the adsorption ability was studied using an azo dye Acid Orange 7 (AO7) as a model compound. The highest sorption efficiency towards AO7 exhibited sorbents prepared at temperatures below 700°C, which was attributed mainly to the presence of hydroxyl groups on the oxide surface. A strong correlation was found between an adsorption efficiency of cerium oxides and their degradation efficiency for organophosphate pesticide parathion methyl. The >Ce–OH groups on the sorbent surface are responsible for the dye binding by the surface-complexation mechanism, and probably also for the nucleophilic cleavage of the P–O–aryl bond in the pesticide molecule.